Prioritizing Infrastructure Investments : A Comparative Review of Applications in Chile - Marcelo, Darwin; House, Schuyler; Raina, Aditi (World Bank, Washington, DC, 2018)
Governments worldwide face the difficult challenge of deciding which infrastructure projects to prioritize and select for implementation, given the limits of available funding and the need to attain their developmental goals. The key objective of this report is to conduct a comparative exercise between the World Bank's Infrastructure Prioritization Framework, a multicriteria analysis–based methodology to project prioritization, and a more complex cost-benefit analysis–based approach. The report focuses on Chile, which has a well-institutionalized evaluation process that uses cost-benefit analysis to assess projects on their quality and ability to generate value for money. The analysis compares the results of the Infrastructure Prioritization Framework alongside Chile's current cost-benefit analysis–based and multicriteria analysis approaches to the same subsets of projects in the road transport and water reservoir subsectors, respectively. The results show that the Infrastructure Prioritization Framework has application beyond its original proposition and can complement a traditional cost-benefit analysis by directly considering social and environmental policy goals that are otherwise difficult to quantify in a cost-benefit analysis. The analysis also finds that in Chile there is a discrepancy between the stated goals and objectives of the appraisal system and the actual implementation. In the case of transport sector projects, there is an evident deviation between cost-benefit analysis–based selection policy and actual decisions made for project implementation. In the case of water catchment selection, there is a bias toward projects with higher financial-economic performance as compared to social-environmental performance, despite policy intentions to afford consideration to environmental and social development goals.